The perceived built environment and general physical activity: An exploratory study in Jordan - Saadeh, Rami; Obaidat, Ahmed; Allouh, Mohammed Z. (Frontiers in Sustainable Cities, 2022)
The built environment affects the health and wellbeing of the population. The main purpose of this study was to explore the association between the perceived built environment and general physical activity among Jordanians. This cross-sectional study was conducted in Jordan between August and November of 2019 using an online self-administered questionnaire distributed to Facebook groups that are commonly used among the Jordanian population. Descriptive statistics using chi–square test of independence was used to examine the relationship of demographic information and the perceived built environment with physical activity. A total of 1,124 participants were involved in the study with the majority being middle-aged (91.5%), females (67.7%), undergraduates (68.1%), and living in urban areas (71.2%). Most study participants (68.2%) were neither physically active ‘at least two times per week’ nor using parks for routinely physical activity (82.5%). Regarding the association of demographic information with physical activity, gender was significantly associated with weekly physical activity, whereas age and monthly income were significantly associated with routine walking or biking. Further, gender, residency, and monthly income were significantly associated with physical activity at the park (p-value ≤0.05). On the other hand, the availability of specific biking paths, having good and accessible places for physical activity were among the built environment factors that were significantly associated with weekly physical activity (p-value≤0.05). Some characteristics of the perceived built environment were associated with physical activity. Therefore, enhancing the built environment is considered a cornerstone in any national health behavior plan that includes physical activity as one of its components.